Existentialism in Education - Koirala, Matrika Prasad (Academic Voices: A Multidisciplinary Journal, 2011)
This paper is an attempt to survey the historical development of existentialist philosophy, meaning of existence, its philosophical premises and perspectives. Further, this also deals with implications of existentialism in selection of aim of education, organization of curriculum, role of teachers and students and school organization. Keywords Existence, nihilistic, being-in-itself, being-for-itself, individuality DOI: http://dx.doi.org/10.3126/av.v1i0.5309 Academic Voices 2011; 1: 39-44